2019
DOI: 10.4103/ipj.ipj_59_19
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity a risk to depression? A cross-sectional study

Abstract: Background:Depression and obesity are disorders of stress with a dose dependent relationship between the both. The adverse health and social consequences are significant, when depression and obesity co-exist. This study aimed to examine the prevalence of depression among overweight and obese patients in a large station of Armed Forces and associate other risk factors of depression.Methods:This cross sectional descriptive study was conducted in the general OPD of large Station medicare centre (SMC) on overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A recent study in India reported similar findings. They recommended lifestyle modifications and mental health promotion programs as the primary intervention for obese people with a mild risk of developing depression [ 15 ]. They also recommended psychological counseling for obese participants with moderate to severe risk for depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in India reported similar findings. They recommended lifestyle modifications and mental health promotion programs as the primary intervention for obese people with a mild risk of developing depression [ 15 ]. They also recommended psychological counseling for obese participants with moderate to severe risk for depression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, A cross-sectional study was done in 2019 to measure the association between obesity and depression. The study concluded a significant association between these two variables and advanced age (p=0.008) [ 15 ]. Furthermore, another study was done in Al Kharj, Saudi Arabia, reported a significant association between obesity and psychological stress, which was more marked in participants above 30 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that among overweight participants, 12% had depression, whereas 23% of depression was seen in obese participants [ 24 ]. A cross-sectional study by Garg et al from India reported that 12% of participants had moderate depression, whereas 54% had mild depression [ 25 ]. Our results were supported by a cross-sectional study from Abha, Saudi Arabia, which found that 42.7% of participants had moderate to severe depression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reasons to support that antidepressants may increase the risk of breast cancer, the results of many clinical trials have yielded different results. This may have been confounded by a number of confounding factors, for example, depression and obesity are often combined, and obesity is a high risk factor for breast cancer [ 11 13 ]. It may be that people taking antidepressants have high risk factors such as alcohol abuse and high BMI levels that can cause breast cancer [ 14 ], which are difficult to avoid.…”
Section: Introductionmentioning
confidence: 99%